1995
DOI: 10.1177/00220345950740060301
|View full text |Cite
|
Sign up to set email alerts
|

Failure of All-ceramic Fixed Partial Dentures in vitro and in vivo: Analysis and Modeling

Abstract: Hertzian cone cracks visible at the loading site of 20 all-ceramic fixed partial dentures (FPDs), tested in vitro, led to the hypotheses that failure was due to the propagation of localized contact damage crack systems (Hertzian stress state) and that such damage was an unlikely clinical failure mode. Fractographic analysis of the 20 laboratory-failed and nine clinically-failed all-ceramic FPDs allowed for definitive testing of these hypotheses and a comparison between in vitro and in vivo failure behavior. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
201
6
14

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 302 publications
(246 citation statements)
references
References 10 publications
19
201
6
14
Order By: Relevance
“…It is uncertain whether data obtained from the in vitro studies are clinically relevant [16,17]. Wear is a progressive phenomenon associated with several factors [18].…”
Section: Introductionmentioning
confidence: 99%
“…It is uncertain whether data obtained from the in vitro studies are clinically relevant [16,17]. Wear is a progressive phenomenon associated with several factors [18].…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Core ceramics are generally high elastic modulus, high strength materials compared with veneering ceramics. Stress distributions and failure behavior are different in laminate structures, comprised of materials with different elastic properties, than in homogenous structures.…”
Section: Introductionmentioning
confidence: 99%
“…3 In addition, studies testing the porcelain-to-metal bond strength suggest that shear bond strength (SBS) equal to the shear strength of the veneering porcelain provided an adequate bond. 4 In a study by Kelly et al 5 on the failure behavior of In-Ceram fixed partial dentures, it was reported that failure occurred in the connectors, none from contact damage, with approximately 70% to 78% originating from the core/veneer interface, indicating that the interface was a location of high tensile stress, in part due to the elastic modulus mismatch across the interface and the presence of structural flaws. The survival of multimaterial clinical structures is also influenced by material thickness ratios, geometric design factors, processing variables, thermal properties, and mechanical and elastic properties of component materials.…”
mentioning
confidence: 99%
See 2 more Smart Citations